Renewal of functions of lumbar department of spine for judoists facilities of physical rehabilitation - Oleynikova K.A (Kharkov National Pedagogical University, 2010)
Researches of functional state of lumbar department of spine are conducted for sportsmen. 16 judoists of 18-22 years took part in research. Sportsmen drew on the complex of restoration measures within the framework of training process for the improvement of the functional state of lumbar department of spine. It is set that in trainings employments of judoists it is necessary to include such facilities of physical rehabilitation: exercises on flexibility and strengthening of muscles on all perimeter, different methods developed endurance, force and mobility of lumbar department of spine, massage.